Optimalisasi Pemasaran Media Sosial Tiktok Dan Pelatihan Tiktok Shop Di Desa Bernung Pesawaran - Sari, Aida; Ramelan, Mudji Rachmat; Nabila, Nuzul Inas; Marvinita, Risda (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2024)
Emping is a sort of dish prepared from melinjo fruit, which is highly common in Indonesia due to its distinct flavor and ease of production. In Bernung Village, Pesawaran Regency, it is also a home industry. The potential for the emping snack business in Bernung Village is quite large, but this is not matched by the community's knowledge and skills in mastering technology and using the right information technology, particularly digital marketing, which truly helps home industries expand their marketing reach and increase their sales results. The strategy employs a participative approach through training partners. In order to optimize marketing, the stages of this program are based on field conditions in the emping melinjo house business in Bernung village, specifically in Taman Rejo hamlet. Material supply, mentoring, and development are among the steps. The educational results from the post-test results obtained that 70% of participants were able to answer questions correctly, were able to demonstrate operational applications using social media, and participants were already practicing the use of digital content on social media were said to be successful, as seen in the enthusiasm and motivation of the participating business actors to continue marketing online.            Keywords: emping melinjo; home industry; social media; tiktok content